FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN BADAN USAHA MILIK DESA DI KABUPATEN BADUNG - Ida Bagus Putu Purbadharmaja; I Made Putra Yasa; Putu Hedi Sasrawan (Nusantara Hasana Journal, 2023)
BUMDes is a social enterprise, which is a business entity with a social mission in the existence of goals and generating profits to address the needs of social missions. The purpose of this study was to determine the factors that affect the income of Village-Owned Enterprises in Badung Regency. Quantitative research that is associative. Research uses primary data. The sample in this study were 46 Directors of BUMDes in Badung Regency. Data collection was carried out by means of structured interviews. Data analysis using Partial Least Square. The results of the analysis stated that Capital had a positive and significant effect on Bumdes income. Financial management has a positive and significant effect on Bumdes income. entrepreneurial networking has a positive and significant effect on Bumdes income. The variable that has the dominant influence on BUMDes revenue in Badung Regency is entrepreneurial networking. The advice given to BUMDes managers is that in using capital it is expected to carry out coordination to coordinate well with the village administration, village assistants and the Community and Village Empowerment Service so that they comply with applicable regulations. Adjust financial reports in accordance with PERMENDESA 3 of 2021 and Indonesian Government Regulation Number 11 concerning Village-Owned Enterprises. For the Regency Government and the Badung Regency Community and Village Development Service to provide assistance and technical guidance related to the management of BUMDes for business continuity